Pulmonary Sequestration Presenting as an Esophageal Submucosal Tumor - Kao, Ming-Wei; Tsai, Jia-Huei; Lee, Jang-Ming (The Thoracic and Cardiovascular Surgeon, 2013)
Pulmonary sequestration is a congenital anomaly of the lungs. We present the case of a patient whose initial symptom was mild dysphagia. Esophagoscopy showed the presence of a submucosal tumor in the lower-third section of the esophagus. The tumor was excised via video-assisted thoracoscopic surgery. The histopathology results indicated extrapulmonary sequestration. To our knowledge, such a case of extralobar sequestration presenting as an esophageal submucosal tumor has not yet been reported.
Keywords: lung; benign or congenital lesions; pathology